Analysis of Language Policy and Language Ideology in Medan City Public Spaces: A Study of Linguistic Landscape - Mandra, Mandra Saragih; Harisma, Rita; Khairun Nissa; Toni Suhendra Saragih, M Afiv (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the realization of language policy and language ideology reflected in the linguistic landscape of Medan City's public space. Using a mixed methods approach and an explanatory sequential design, this study integrates quantitative data from the documentation of 300 written texts in five sub-districts and qualitative data from interviews with stakeholders and analysis of policy documents. The results show the dominance of Indonesian (42.7%), followed by multilingual texts (34.7%) and texts in foreign languages such as English and Mandarin (18.3%). There is a discrepancy between the national language policy and linguistic practices in the public sphere, especially in the commercial sector where many foreign languages are used for pragmatic economic reasons. Three dominant language ideologies were found, namely language nationalism, economic pragmatism, and ethnic identity, which compete with each other in influencing language practices. This research demonstrates the dialectical relationship between language policy, language ideology and linguistic practice, and emphasizes the importance of an inclusive and adaptive policy approach to the linguistic diversity of multiethnic societies. The findings contribute to the development of a more contextualized and effective theory of linguistic landscapes and language policy practices.